Reassessing the Influence of Parents and Advertising on Children's BMI. Issue 3 (2nd September 2019) - Zeiss, Jessica; Walker, Doug; Carlson, Les
Abstract: With many rendering child obesity as a national priority, researchers are calling for transformative approaches to investigating the precursors of child obesity, including persuasion, and parental and media socialization, among others. This research utilizes a matched child-parent survey to test a multifaceted model of child obesity, with child reports on targeted food advertising evidencing marketplace influences. Findings support the proactive role that parents assume based on their perceptions of the inappropriateness of child-targeted food marketing. While this parental response is negatively related to children's body mass index (BMI), the promising relationship is attenuated by the extent of child exposure to food marketing.